Spatial Analisys of Physical Characteristics of Jatiroke Water Catchment Area Jatinangor Districs - Suryadi, Edy; Julinah, Siti; Amaru, Kharistya (Jurnal Agrotek Ummat, 2022)
This research aim to identify the characteristics catchment area of jatiroke and present in the form of spatial data. The descriptive method was employed in this study. The results showed of Jatiroke catchment area was 5695,80 ha. Schmidt-Ferguson and Oldeman's classification of climate puts the climatic characteristics of the Jatiroke catchment area in the same group as type C and type C3. The Jatiroke catchment area has an elongated and narrow shape (like a bird feather), which impacts the amount of water that enters the river. The Jatiroke catchment area has an elongated and narrow drainage pattern and is shaped like a bird's feather based on the characteristics of the watershed. Land cover in the Jatiroke catchment area is dominated by forest mixed covering an area of 1615 ha with a percentage of 28%. Andosol and Kambisol soil types are found in the Jatiroke catchment area. Kambisol soil type dominates with an area of 3245.57 ha with a percentage of 57% of the total area. The slope of the Jatiroke catchment area is dominated by moderately steep and steep slope classes with an area of 3905.4 ha and 3278.2 ha, respectively, with an area presentation of 27.75% and 23.29%.